Consideration of Clinician and Researcher Opinions on the Parameters of Nonsuicidal Self-Injury Disorder Diagnostic Criteria. (February 2021) - Ammerman, Brooke A.; Lengel, Gregory J.; Washburn, Jason J.
Highlights: Uncertainty about nonsuicidal self-injury (NSSI) disorder parameters exists Clinician and researcher opinions can improve the clinical utility of NSSI disorder Four days of NSSI in the past one-month may enhance NSSI disorder clinical utility Helpfulness of diagnostic specifiers and exclusionary criteria were supported Diagnostic category considerations include Disruptive, Impulse-Control and Conduct Disorders Abstract: Nonsuicidal self-injury (NSSI) disorder represents an opportunity to address the significant costs associated with NSSI; however, there is a need to resolve the uncertainty regarding specific parameters of the diagnostic criteria to ensure clinical utility. As such, to better understand the clinical applicability, and guide future research in this area, clinicians and researchers in the field of NSSI (n=112) completed an anonymous online survey assessing their opinions regarding several aspects of NSSI disorder. Results highlight that past-month NSSI was the most frequently endorsed timeframe required for a NSSI disorder diagnosis. There was support for the clinical usefulness of several specifiers and general consensus regarding exclusion criterion. Finally, Disruptive, Impulse-Control and Conduct Disorders was considered to be the most appropriate diagnostic category. Our findings suggest that requiring four days of NSSI in the past one-month may enhance the clinical utility of NSSI disorder. Results also offer guidance on additional aspects of the diagnostic criteria to better describe and conceptualize NSSI disorder for research and clinical applications.